积分推导三角函数转复数

2019/01/02 11:23
阅读数 69

欲推结论:

  $\int_{0}^{\infty } cosbx·e^{-a^{2}x^{2}}dx = \frac{\sqrt{\pi}}{2a}e^{-\frac{b^{2}}{4b^{2}}}$

已知定理:

  1.欧拉函数:$e^{i\theta} = cos\theta + sin\theta$ , $e^{-i\theta} = cos\theta - sin\theta$

  2.$\int_{0}^{\infty }e^{-a^{2}x^{2}}dx = \frac{\sqrt{\pi}}{2a}$ (证明参考这里)

推导:

  $\int_{0}^{\infty } cosbx·e^{-a^{2}x^{2}}dx $

  $= \frac{1}{2}\int_{0}^{\infty }(e^{-a^{2}x^{2}+ibx} + e^{-a^{2}x^{2}-ibx})dx$

  $= \frac{1}{2}\int_{0}^{\infty }(e^{-(ax-\frac{ib}{2a})^{2} - \frac{b^{2}}{4a^{2}}} + e^{-(ax+\frac{ib}{2a})^{2} - \frac{b^{2}}{4a^{2}}})dx$ 

  $= \frac{1}{2}e^{- \frac{b^{2}}{4a^{2}}}\int_{0}^{\infty }e^{-(ax-\frac{ib}{2a})^{2}}dx + \frac{1}{2}e^{- \frac{b^{2}}{4a^{2}}}\int_{0}^{\infty }e^{-(ax+\frac{ib}{2a})^{2}}dx$

  $= \frac{\sqrt{\pi}}{2a}e^{-\frac{b^{2}}{4b^{2}}}$

展开阅读全文
cos
打赏
0
0 收藏
分享
加载中
更多评论
打赏
0 评论
0 收藏
0
分享
返回顶部
顶部